Association of combined complement factor H Y402H and ARMS2/LOC387715 A69S polymorphisms with age-related macular degeneration: an updated meta-analysis - Jabbarpoor Bonyadi, Mohammad Hossein; Yaseri, Mehdi; Soheilian, Masoud (Ophthalmic genetics, 2020)
Complement factor H (CFH) Y402 H (rs1061170) and age-related maculopathy susceptibility2 (ARMS2)/LOC387715 A69 S (rs10490924) polymorphisms shown to have significant association with AMD. In this meta-analysis, we updated and pooled the results of available association studies between combined ARMS2/LOC387715A69 S-CFHY402 H genotypes and AMD to estimate the synergistic effects. Heterogeneity of studies was evaluated using Cochran Q-test and I-square index. To modify the heterogeneity in the variables we used random effects model. Meta-analysis was performed using STATA. To estimate the additive or supra-additive effects we calculated RERI (relative excess risk due to interaction), AP (attributable proportion due to interaction), S (synergy index) and V (multiplicative index). We included 12 studies with 4668 AMD patients and 4936 control subjects. Considering the GGTT genotypes as reference line, the pooled AMD odds ratios for stratified combined genotypes was 2.13 (95% CI 1.64-2.78) for GGnonTT, 2.17 (95% CI 1.63-2.89) for nonGGTT and 7.23 (95% CI 4.95-10.55) for nonGGnonTT. Pooled synergy analysis revealed RERI = 3.90 (95% CI 0.58-10.03), AP = .53 (95% CI 0.09-0.69), S = 2.57 (95% CI 1.27-5.22) and V = 1.47 (95% CI 1.21-1.80). This updated analysis showed a strong synergistic and positive multiplicative effect of these two genes indicating that there is common pathway of ARMS2/LOC387715 A69 S and CFH Y402 H in AMD pathogenesis which may be complement system pathway.